2021
DOI: 10.3389/fimmu.2021.758451
|View full text |Cite
|
Sign up to set email alerts
|

A Novel TLR4-Binding Domain of Peroxiredoxin From Entamoeba histolytica Triggers NLRP3 Inflammasome Activation in Macrophages

Abstract: Macrophages promote early host responses to infection by releasing pro-inflammatory cytokines, and they are crucial to combat amoebiasis, a disease affecting millions of people worldwide. Macrophages elicit pro-inflammatory responses following direct cell/cell interaction of Entamoeba histolytica, inducing NLRP3 inflammasome activation with high-output IL-1β/IL-18 secretion. Here, we found that trophozoites could upregulate peroxiredoxins (Prx) expression and abundantly secrete Prxs when encountering host cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“… 32 The C-terminal domain of peroxiredoxin in anaerobic parasitic amoebozoan, Entamoeba histolytica , also triggered TLR4-dependent activation of NLRP3 inflammasome in macrophages through caspase-1-dependent canonical pathway. 50 The mechanism of immune response activation following r Lv Prx4 injection may involve the regulation of antimicrobial peptides and interferons through Toll pathway as the presented data indicate that r Lv Prx4 injection could not promote the expression of LvPEN4 and LvVago5 when LvTLR1 or LvTLR2 was inhibited ( Figure 8 ). Of interest, LvALF AA-K was overexpressed in r Lv Prx4-injected shrimp and was upregulated despite silencing of the toll-like receptor.…”
Section: Discussionmentioning
confidence: 91%
“… 32 The C-terminal domain of peroxiredoxin in anaerobic parasitic amoebozoan, Entamoeba histolytica , also triggered TLR4-dependent activation of NLRP3 inflammasome in macrophages through caspase-1-dependent canonical pathway. 50 The mechanism of immune response activation following r Lv Prx4 injection may involve the regulation of antimicrobial peptides and interferons through Toll pathway as the presented data indicate that r Lv Prx4 injection could not promote the expression of LvPEN4 and LvVago5 when LvTLR1 or LvTLR2 was inhibited ( Figure 8 ). Of interest, LvALF AA-K was overexpressed in r Lv Prx4-injected shrimp and was upregulated despite silencing of the toll-like receptor.…”
Section: Discussionmentioning
confidence: 91%
“…Since we found that ROS expression is reduced in NLRP3-depleted macrophages, it may be interesting to examine the changes in MPO in a future study. The Toll-like receptor 4 (TLR4) and nuclear factor kappa B (NF-kB) pathways play a crucial role in the innate immune response to bacterial LPS (28). This pathway is activated when TLR4 recognizes LPS and triggers NF-kB, which then regulates the expression of proinflammatory cytokines and other genes involved in the immune response, likely through the NLRP3 protein (28).…”
Section: Discussionmentioning
confidence: 99%
“…The Toll-like receptor 4 (TLR4) and nuclear factor kappa B (NF-kB) pathways play a crucial role in the innate immune response to bacterial LPS ( 28 ). This pathway is activated when TLR4 recognizes LPS and triggers NF-kB, which then regulates the expression of pro-inflammatory cytokines and other genes involved in the immune response, likely through the NLRP3 protein ( 28 ). In the absence of NLRP3, the activation of the TLR4/NF-kB pathway in macrophages may be diminished or altered, leading to changes in the expression of pro-inflammatory cytokines and other immune response genes ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adhesion of amoebic trophozoites to colonic epithelial cells mainly depends on the Gal/GalNAc lectins ( 5 , 11 , 26 ). Once amoeba trophozoites adhere to host cells, a series of amoebic reactions are triggered, including the release of amoebapore, cysteine proteases, and peroxiredoxin, as well as trogocytosis, contributing to cell killing and tissue invasion ( 8 , 9 , 15 , 27 , 28 ). Our research lines focus on how host cells respond before apoptosis or phagocytosis induced by E. histolytica trophozoites.…”
Section: Discussionmentioning
confidence: 99%